HUBUNGAN PENGETAHUAN DAN PERSEPSI PASIEN BPJS DENGAN PELAYANAN KESEHATAN BPJS DI RUANG RAWAT INAP KELAS III RSUD RADEN MATTAHER JAMBI - Giatno Putra; Arifarahmi Arifarahmi; Elis Suryani Purba (Jurnal Akademika Baiturrahim Jambi, 2016)
Backround : Health care is a public demand for health care in accordance with professional standards were good. BPJS (Implementation of the Social Security Agency) is conducting a program of health insurance for the entire population of Indonesia. Problems that occur in society today is the lack of knowledge about this BPJS services giving rise to different perceptions of the community. The formulation of this research is How Relationship Knowledge and Perceptions of Patients BPJS with Health Services Inpatient BPJS in Class III General Hospital Raden Mattaher Jambi.Method : This research is a quantitative research with cross sectional study design that aims to determine the relationship BPJS Knowledge and Perceptions of Patients with Health Services Inpatient BPJS in Class III General Hospital Raden Mattaher Jambi. Analysis of the data used is univariate and bivariate statistical test using Chi Square. Location research in hospitals Radden Mattaher 1- Jambi conducted on August 6, 2015. The population in this study were class III inpatients using health BPJS amounted to 7950 people. The sampling technique used is proportional random sampling using the formula can lomesshow in a sample of 49 people. Result : From the research there is a relationship between knowledge BPJS patients with health care BPJS In class III installation Inpatient General Hospital Raden Mattaher Jambi, with p_Value value of = 0.002 (p-value ≤ 0.05).Expected to hospitals Radden Jambi Mattaher can improve the quality of health services, especially to improve services and satisfaction for patients undergoing inpatient care so that health services provided may provide optimal results.Keywords: Knowledge, Perception, and Health Services BPJS